1-6(-8k-2)=109

Simple and best practice solution for 1-6(-8k-2)=109 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-6(-8k-2)=109 equation:


Simplifying
1 + -6(-8k + -2) = 109

Reorder the terms:
1 + -6(-2 + -8k) = 109
1 + (-2 * -6 + -8k * -6) = 109
1 + (12 + 48k) = 109

Combine like terms: 1 + 12 = 13
13 + 48k = 109

Solving
13 + 48k = 109

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 48k = 109 + -13

Combine like terms: 13 + -13 = 0
0 + 48k = 109 + -13
48k = 109 + -13

Combine like terms: 109 + -13 = 96
48k = 96

Divide each side by '48'.
k = 2

Simplifying
k = 2

See similar equations:

| 8y+96=3y-9 | | x=23000-(x(.12))+(x(.05)) | | 2m+5=8 | | a+14=17 | | x=23-(x(.12))+(x(.05)) | | log(x)+log(x^4)=5 | | 92=-(-5x-4)+6x | | 3(3a-4)=-84 | | 7a^2-14a=21 | | -8(7k+1)=216 | | 5x-2x*x=2 | | logx+logx^4=5 | | 3v^2-36=3v | | (9/10)/3 | | 12=-8x-4x | | (x-1)(x-2)(x-3)(x-4)=24 | | 21=1+3k-8k | | 22=1+4p-7 | | 13=5(1+4M)-2 | | 2/7-1/7=3/14 | | 8x-7y+17=0 | | (6y-5p)(y)=(3p)(2p) | | [(2q-3r)-5][(2q-3x+5)]= | | 5(2x-5)=1.5(18x+40) | | 8cos(2x)=5 | | 32-5m= | | 5(v-8)-6=-4(-5v+9)-7 | | (t-4)(4)+(t-1)(4)=(5)(t-1)(t-4) | | sinx=(x^2)/(625pi^2) | | 7=2b-8+1 | | 7.6x-3.4=11.8 | | -5(3n+3)=10 |

Equations solver categories